Evaluation of pediatric migraine triggers: a single-center study - Hey-Joon Son; Joo-Ok Jin; Kon-Hee Lee (Clinical and Experimental Pediatrics, 2025)
Background Pediatric migraines are primarily treated with medications. However, recognizing the triggers related to patient behaviors and lifestyle is also important. Purpose This study aimed to evaluate the factors that trigger pediatric migraines. Methods This study included 102 pediatric patients with migraine diagnosed using the third edition of the International Classification of Headache Disorders who visited our pediatric headache clinic between November 2021 and October 2022. We reviewed the patients’ clinical features, imaging studies, screening tests for behaviors and emotions, and questionnaires regarding triggers. Statistical analyses were performed using the independent sample Student t test and linear-by-linear association test. Results The 102 patients (44 males, 58 females; mean age, 12.0±2.9 years) were classified into migraine without aura (n=58) and migraine with aura (n=44) groups. Sleep disturbances were the most frequent trigger (76.5%). Other triggers included academic stress (66.7%), motion sickness (62.7%), and fatigue (52.9%). Academic stress was the most significant trigger for pain severity in 44.1% of patients. Abnormal behavioral or psychiatric assessment results were associated with a higher number of triggers. Conclusion This study identified sleep disturbance and academic stress as common triggers of pediatric migraine, with academic stress being the most intense. Clinicians should understand these triggers and advise patients to avoid them by changing their lifestyles, if possible.